2013
DOI: 10.5946/ce.2013.46.2.193
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous Inflammation in Terminal Ileum Presenting as an Appendiceal Mass: Case Report and Review of the Literature

Abstract: Xanthogranulomatous inflammation (XGI) is a rare benign inflammatory disease characterized by aggregation of lipid-laden foamy macrophages. This disease entity has been described in various organs but most commonly in the kidney and gallbladder. The occurrence of this disease in the lower gastrointestinal tract is extremely rare. Its clinical importance is that it can be misdiagnosed as an infiltrative cancer. In this case report, a 52-year-old male complained of right lower quadrant abdominal pain for a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Xanthomatosis is characterized by accumulation of lipid-laden, foamy macrophages resulting in nodule formation and commonly involving the skin [ 4 ]. In the gastrointestinal tract, stomach is the most frequent location; however, cases involving esophagus [ 5 ], small bowel [ 6 , 7 ], ileocecal valve [ 8 ], colon [ 9 12 ] and rectum [ 13 ], tendons, bladder, and prostate have been described [ 14 ]. We report a case of SBO due to intestinal xanthomatosis.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthomatosis is characterized by accumulation of lipid-laden, foamy macrophages resulting in nodule formation and commonly involving the skin [ 4 ]. In the gastrointestinal tract, stomach is the most frequent location; however, cases involving esophagus [ 5 ], small bowel [ 6 , 7 ], ileocecal valve [ 8 ], colon [ 9 12 ] and rectum [ 13 ], tendons, bladder, and prostate have been described [ 14 ]. We report a case of SBO due to intestinal xanthomatosis.…”
Section: Introductionmentioning
confidence: 99%
“…Histological examination of these cases did not support continuity between the xanthogranuloma and adenocarcinoma. In the other case of XGI in the terminal ileum reported by Yoon et al, 2 preoperative endoscopy and biopsy showed ulcers with acute and chronic inflammation only. However, surgical resection was considered unavoidable in view of the radiological findings highly suggestive of appendiceal cancer.…”
Section: Discussionmentioning
confidence: 78%
“…1 The disease process was most frequently reported in the kidney and gallbladder. Rare occurrence in the gastro-intestinal tract was illustrated in only one recently reported case in the terminal ileum, 2 four reported cases in the colon, [3][4][5][6] eight cases in a series of interval appendicectomy specimens, 7 and eight cases with gastric involvement. [8][9][10][11][12][13] Of the four cases with colonic involvement, two involved the sigmoid colon, 3,4 one involved the caecum, 5 and one involved the ascending colon.…”
Section: Introductionmentioning
confidence: 99%
“…The xanthogranulomatous lesion is a rare chronic inflammatory disease characterized by the focal or diffuse destructive inflammatory process, with accumulation of lipid-laden fibrous tissue, and acute and chronic inflammatory cells; It may involve any organ, but the most common sites are known as the gallbladder and kidney [8]. The xanthogranulomatous inflammation involving the salpingitis and cystitis simultaneously is very rare.…”
Section: Discussionmentioning
confidence: 99%